1993
DOI: 10.1101/gad.7.3.454
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the mouse agouti gene predicts a secreted protein ubiquitously expressed in mice carrying the lethal yellow mutation.

Abstract: The mouse agouti gene controls the deposition of yellow and black pigment in developing hairs. Several dominant alleles, including lethal yellow (AY), result in the exclusive production of yellow pigment and have pleiotropic effects that include obesity and increased tumor susceptibility. In an interspecific backcross, we established genetic limits for the agouti gene and found that the A y and the lethal non=agouti (a'q allele were not separated from a previously identified probe at the breakpoint of the IslG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
279
0
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(287 citation statements)
references
References 70 publications
4
279
0
2
Order By: Relevance
“…Furthermore, the results presented here show that mature A y /a mice are hyperinsulinemic and hyperleptinemic. This is also in line with previous findings (3,7,16,30), although these characteristics were milder in A y /a mice than in ob/ob mice (with the exception of hyperleptinemia). In the present study, we were not able to assess CART or AGRP protein levels and/or activity, because the amount of total protein recovered was too small.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, the results presented here show that mature A y /a mice are hyperinsulinemic and hyperleptinemic. This is also in line with previous findings (3,7,16,30), although these characteristics were milder in A y /a mice than in ob/ob mice (with the exception of hyperleptinemia). In the present study, we were not able to assess CART or AGRP protein levels and/or activity, because the amount of total protein recovered was too small.…”
Section: Discussionsupporting
confidence: 82%
“…Agouti protein has a potent antagonistic effect on hypothalamic MC4R (7, 30), and rodents become hyperphagic when signaling is interrupted (19,31). Lethal yellow (A y /a) mice display ectopic overexpression of agouti protein in the brain, which results in defective proopiomelanocortin (POMC)/MC4R signaling and, upon maturation, obesity (7,16,30,44). Because these obese mice are both hyperleptinemic and insensitive to exogenous leptin treatment (16, 44), they are thought to be in a "leptin-resistant state."…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several mutations in mouse genes that lead to obesity have recently been characterized at the molecular level (1)(2)(3)(4)(5)(6)(7)(8). Further analysis of these genes and the use of mouse lines with mutations in these genes provides an opportunity to identify new therapeutic targets for the treatment of human obesity.…”
mentioning
confidence: 99%
“…Most studies have proposed that ASP acts as an antagonist of MC1R, causing MC1R desensitization and consequent reduction of tyrosinase activity. 4,17 However, Scott et al 18 observed that ASP plays a role in the regulation of skin pigmentation through downregulation of MC1R mRNA transcription in cultured human melanocytes. Recently, microphthalmia transcription factor (MITF), which belong to the basic helix-loop-helix family, was found to regulate the gene for MC1R through its promoter region in cultured cells.…”
Section: Seeing the Gene Therapy C-h Yang Et Almentioning
confidence: 99%